2010
DOI: 10.1128/jvi.01700-10
|View full text |Cite
|
Sign up to set email alerts
|

Cascade of Events Governing Cell-Cell Fusion Induced by Herpes Simplex Virus Glycoproteins gD, gH/gL, and gB

Abstract: Herpesviruses minimally require the envelope proteins gB and gH/gL for virus entry and cell-cell fusion; herpes simplex virus (HSV) additionally requires the receptor-binding protein gD. Although gB is a class III fusion protein, gH/gL does not resemble any documented viral fusion protein at a structural level. Based on those data, we proposed that gH/gL does not function as a cofusogen with gB but instead regulates the fusogenic activity of gB. Here, we present data to support that hypothesis. First, receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
247
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(258 citation statements)
references
References 44 publications
11
247
0
Order By: Relevance
“…Given our rudimentary understanding of how the 4 essential glycoproteins interact, it is premature to speculate how this potentially common trigger promotes one event but not the other depending on the particular mutant glycoprotein. While recent reports have suggested that gB is the fusogen in HSV entry and spread, whereas gH serves a regulatory function (30), much of the evidence comes from virus-free systems that do not clearly distinguish between entry and spread (30,34,35). In fact, the virus-free cell fusion assay in our study reflected the activities of gB:NT and gH:KV in spread but not in entry, supporting the view that this assay is limited as a model for HSV entry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given our rudimentary understanding of how the 4 essential glycoproteins interact, it is premature to speculate how this potentially common trigger promotes one event but not the other depending on the particular mutant glycoprotein. While recent reports have suggested that gB is the fusogen in HSV entry and spread, whereas gH serves a regulatory function (30), much of the evidence comes from virus-free systems that do not clearly distinguish between entry and spread (30,34,35). In fact, the virus-free cell fusion assay in our study reflected the activities of gB:NT and gH:KV in spread but not in entry, supporting the view that this assay is limited as a model for HSV entry.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence indicated that gH/gL could carry out hemifusion, an intermediate state in which the outer membrane leaflets of the target and viral membranes mix, whereas both gB and gH/gL were required for complete fusion (32), but these findings were recently called into question (33). Recent studies suggested that gH/gL activates the dormant fusogenic activity of gB in response to signaling by receptor-bound gD (30,34,35), indicating that gH/gL performs an intermediate regulatory function in the steps leading to membrane fusion. However, since these studies were performed in virus-free cell fusion systems, it is unclear whether they apply equally to virus entry and spread.…”
mentioning
confidence: 99%
“…Soluble gD (gD t ) rescued the infection of gD −/− virions, providing indirect evidence that gD undergoes conformational changes upon interaction with receptor-positive cells (16). gH t /gL can promote cell-cell fusion in cells expressing gD (or exposed to gD t ), gB, plus gD receptor (19). gH t /gL rescues the infection of gH −/− EBV virions (34).…”
Section: Dissociation Of Gl Occurs If Nectin1 Gd and Gb Are Presentmentioning
confidence: 99%
“…The role of gH/gL in fusion is less clear because crystal structures of herpes simplex virus 2 (HSV-2), pseudo-rabies virus (PrV), and Epstein-Barr virus (EBV) gH/gL did not reveal any similarity to known viral fusion proteins (9)(10)(11). It has been proposed that gH/gL is involved in the entry process through activation of gB (12). In addition to gB and gH/gL, most herpesviruses encode additional glycoproteins that are able to interact with gH/gL and are capable of either mediating binding to specific cellular receptors or regulating the activity of the gH/gL-gB complex (5,6).…”
mentioning
confidence: 99%